Understanding Consumers’ Barriers to Using FinTech Services in the United Arab Emirates: Mixed-Methods Research Approach - Mohamed Bouteraa; Brahim Chekima; Nelson Lajuni; Ayesha Anwar (MDPI, 2023)
The cutting-edge development known as FinTech is now fast replacing traditional financial services all over the world. Despite that, UAE consumers are still not embracing FinTech services at the expected rate. This study hence suggests expanded research based on the unified theory of acceptance and use of technology (UTAUT) to deeply examine the obstacles preventing consumers from using FinTech services. This research utilised an exploratory sequential mixed-method approach. Preliminary semi-structured interviews involving ten banking experts were undertaken to explore the barriers preventing consumers from using FinTech services. To get additional empirical support for the research concept, the study sequentially examined numerous components using a quantitative cross-sectional online survey involving 332 bank customers. The qualitative investigation highlighted six new barriers that consumers face when using FinTech. Through quantitative data analysis, the preliminary qualitative findings were largely verified. As far as the authors are concerned, this inquiry is the first to put forth a thorough model that takes into account organisational, technological, individual, and environmental aspects for addressing the problem of low FinTech usage. By incorporating several new factors, this study also expands the UTAUT. Additionally, it is one of the first studies to examine FinTech adoption employing a mixed-approach methodology.